Effectiveness of Emotional Freedom Technique (EFT) to Reduce Students' Enthusiasm for Mathematics - Suharnadi, Putra; Firman; Netrawati; Rahman, Mohd Nazri Badul (IJER (Indonesian Journal of Educational Research), 2024)
This study aimed to address the issue of math anxiety, a common obstacle affecting students' emotional well-being and academic performance in mathematics. Math anxiety includes feelings of fear, discomfort, and avoidance related to math tasks, and is often categorized as test anxiety, number anxiety, and abstract anxiety. This research explores the effectiveness of the Emotional Freedom Technique (EFT), an alternative treatment method combining psychological and physical approaches, in reducing math anxiety. This study employed a quantitative research design that involved participants experiencing math anxiety. EFT sessions were conducted by guiding participants to tap specific meridian acupuncture points (e.g., the head, eyebrows, temples, and chin) while affirming their emotional concerns about math. Pre- and post-intervention anxiety levels were measured using a validated Math Anxiety Scale. The results revealed a significant reduction in participants’ math anxiety levels after undergoing EFT sessions. Additionally, anxiety-reducing effects were sustained over time, indicating EFT's potential of EFT as a practical tool for managing emotional barriers to learning. This research highlights EFT as an accessible and effective method to support students struggling with math anxiety, contributing to improved emotion regulation and academic success in mathematics.